Impact of Extracurricular Activities on Academic Performance of Students at Secondary Level - Anjum, Shabiha (International Journal of Applied Guidance and Counseling, 2021)
The present study aims to observe the impact of extracurricular activities on the academic performance of students at the secondary level in Multan city. All the students at the secondary level in the public sector of Multan city are the population of this study. Three hundred student’s 9th and 10th classes from (two) secondary schools from Multan city were selected. For this study, the researcher uses a simple random sampling technique. A total of 30 survey questions were developed based on Likert-scale type statement options (SA, A, N, DA, SDA), keeping in mind the objective of the study. The data were tabulated and analyzed by using descriptive statistical techniques. The MS-Excel is used for the descriptive analysis of the data. The study concluded that there is a severe need for the introduction of extracurricular activities, orientation programs for the students of secondary level. Extracurricular activities have a positive influence on students' life by improving their behavior, academic performance, better exam scores, more regular class attendance, a better self-image, due to these aspects which makes the students life more successful. Finally, the study suggests that Government should support the introduction of extracurricular activities in all secondary schools, allocate special funds, appoint special trainers/teachers, and fix their pay equal to other subject teachers.